Rationalization Efforts in the Merger of Public Port Management Organizations - Ramlan Syah; Harmein Nasution; Yeni Absah (Penerbit Goodwood, 2026)
Purpose: This study aims to evaluate how rationalization strategies were applied in the merger of public port management organizations, focusing on KSOP Utama Belawan, to see whether they created a lean, efficient, and adaptive bureaucracy. Methodology/approach: Qualitative descriptive–exploratory case study employed in-depth interviews, non-participant observation, and document analysis with 30 purposively selected informants, data were thematically coded and analyzed using Nvivo12 Results/findings: Rationalization comprised downsizing, job-title simplification, and unit consolidation, formally supported by job and workload analyses (Anjab–ABK), competency mapping, and rotations. Implementation remained predominantly administrative and was not grounded in a systematic postmerger assessment of actual service demands and functional workloads. Consequently, administrative units were overstaffed, technical posts understaffed, competencies misaligned, regulatory updates delayed, and SOPs absent, producing structural and functional misalignment, performance stagnation, and defensive silence. Conclusions: Post-merger rationalization efforts were more administrative than strategic, so the objectives of port bureaucratic reform have not been optimally achieved. Limitations: The study focuses only on KSOP Utama Belawan within 2023–2025 and lacked advanced tools to assess staffing needs quantitatively. Contributions: This study advances public-sector reform literature and guides relevant parties in crafting comprehensive, needs-based rationalization strategies.